Overview of Urban Rail Transport Full Automatic Operation System and Typical Scenario - Wenju TAN; Weifeng YANG; Yun LIAO; Kaicheng ZHOU (机车电传动)
The composition and function for full automatic operation system of urban rail transport were introduced, and the design method and classification basis of operation scenario were emphatically expounded. Finally, some typical scenarios were selected for detailed analysis. Full automatic operation system of urban rail transport is the direction of intelligent and wisdom development in the future and had been opened, constructed or planned in many chinese cities.